2009
DOI: 10.1038/hr.2009.63
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined olmesartan and pravastatin on glucose intolerance and cardiovascular remodeling in a metabolic-syndrome model

Abstract: Hypertension and dyslipidemia frequently coexist in patients with progressive insulin resistance and thus constitute metabolic syndrome. We sought to determine the merits of combining an angiotensin II receptor blocker and a 3-hydroxy-3-methylglutarylcoenzyme A reductase inhibitor in treating this pathological condition. Five-week-old Otsuka Long-Evans Tokushima Fatty rats, a model of metabolic syndrome, were untreated or treated with olmesartan 3 mg kg À1 per day, pravastatin 30 mg kg À1 per day or their comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…37,38 In the present study, short-term treatment with olmesartan significantly decreased plasma triglyceride level, but did not change fat weight, glucose metabolism, and plasma insulin and adiponectin levels in 25-week-age OLETF rats. Thus, it is possible that the renoprotective effect of olmesartan is not mediated through its antimetabolic effect under the present experimental conditions.…”
Section: Discussionsupporting
confidence: 42%
“…37,38 In the present study, short-term treatment with olmesartan significantly decreased plasma triglyceride level, but did not change fat weight, glucose metabolism, and plasma insulin and adiponectin levels in 25-week-age OLETF rats. Thus, it is possible that the renoprotective effect of olmesartan is not mediated through its antimetabolic effect under the present experimental conditions.…”
Section: Discussionsupporting
confidence: 42%
“…A major byproduct of inflammation is fibrosis, which is found in the heart, liver, and kidney in metabolic syndrome models, including the fructose-induced syndrome. [41][42][43] Our study demonstrates that high-fructose diet-induced oxidative stress and inflammation lead to target organ damage in the form of collagen deposition and fibrosis, which also affects the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…A major byproduct of inflammation is fibrosis, which is found in the heart, liver, and kidney in metabolic syndrome models, including the fructose-induced syndrome. [41][42][43] Our study demonstrates that high-fructose diet-induced oxidative stress and inflammation lead to target organ damage in the form of collagen deposition and fibrosis, which also affects the vasculature.Recently, several studies have revealed the relevance of the immune system in the pathogenesis of hypertension and vascular damage.5 Guzik et al 8 demonstrated for the first time that lack of lymphocytes in mice blunts Ang II-induced BP rise and vascular injury, and that adoptive transfer of T cells restores Ang II effects. T lymphocyte populations include T effector lymphocytes (eg, Th1 and Th2) and Treg.…”
mentioning
confidence: 99%
“…As mentioned above, the circulating NEFA level was increased in OLETF rats, and this elevated level was reduced by the treatment with pravastatin. Several reports suggest that pravastatin has beneficial effects in various disease states by using different dose regimens (Glorioso et al 1999, Freeman et al 2001, Yu et al 2004, Chen et al 2007, Kajikuri et al 2009, Koh et al 2009, Mizukawa et al 2009, Ohkawara et al 2010. Indeed, evidence of endothelial dysfunction has been observed in various vessels in states in which there is an increment in the circulating level of free fatty acids (Steinberg et al 1997, Creager et al 2003, Azekoshi et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…A possible interpretation of the present data is that the endothelial dysfunction present in OLETF rats is attributed to an increase in blood NEFA, and that endothelial dysfunction is improved by pravastatin treatment at least in part through a lowering of this parameter. However, to establish a causal relationship and appropriate dose of pravastatin would require research focusing, for example, (1) on time-course alterations both in circulating substances and in endothelial dysfunction in this model because this OLETF rat manifests symptoms of metabolic syndrome (Matsuzaki et al 2008, Mizukawa et al 2009, and (2) on comparison of various doses of pravastatin with regard to the impact on endothelial dysfunction. Moreover, in the present study, we used one dose of pravastatin as reported previously (Kobayashi et al 2000, Rakotoniaina et al 2006.…”
Section: Discussionmentioning
confidence: 99%